[2-(3-Арил-1H-1,2,4-триазол)феніл]аміни: синтез, хімічна модифікація, фізико-хімічні та біологічні властивості синтезованих сполук - Холодняк, Сергій Валерійович; Kholodnyak, S. V. (Запорізький державний медичний університет, 2016)
Дисертаційна робота присвячена розробці препаративних методів синтезу 2-арил-[1,2,4]триазоло[1,5-c]хіназолінів та продуктів їх гідролітичного розщеплення – [2-(3-арил-1,2,4-триазол-5-іл)феніл]амінів, на основі яких вперше синтезовані неописані N-феніл-N'-[2-(3-феніл-1H-1,2,4-триазол-5-іл)феніл]- сечовини, N-[2-(3-феніл-1H-1,2,4-триазол-5-іл)феніл]бензенсульфаміди, 2-арил-5-R-, 2-арил-5-R,5-R1-5,6-дигідро- та 2-арил-6'H-спіро[(циклоалкіл-, гетероцикліл-, гетарил-)]-[1,2,4]триазоло[1,5-c]хіназоліни, 2-арил-4a-R-5,6-дигідропірроло-[1,2-a][1,2,4]-триазоло[1,5-c]хіназолін-7(4aH)-oни, (2-R-7-oксо-4a,5,6,7-тетрагідро-пірроло[1,2-a][1,2,4]триазоло[1,5-c] хіназолін-4a-іл) карбонові кислоти та їх естери. За допомогою квантово-хімічних та спектральних методів обґрунтована динамічна рівновага серед таутомерів 2-(3-арил-1,2,4-триазол-5-іл)феніл]амінів та спрогнозована направленість перебігу реакцій [5+1]-циклоконденсації з різноманітними електрофілами. У процесі виконання роботи синтезовано 138 сполук (126 вперше), серед яких знайдені речовини з високою протимікробною, протигрибковою, цукрознижувальною та протисудомною активністю, а також виявлені певні закономірності зв’язку між хімічною будовою та фармакологічною активністю. The present work is devoted to the elaboration of preparative synthetic protocols for 2-R-[1,2,4]triazolo[1,5-c]quinazolines and products of their hydrolytic cleavage – [2-(3-aryl-1,2,4-trazole-5-yl)phenyl]amines. The latter were used as starting compounds for the synthesis of previously unknown N-phenyl-N'-[2-(3-phenyl-1H-1,2,4-triazole-5-yl)phenyl]ureas, N-[2-(3-phenyl-1H-1,2,4-triazole-5-yl)phynyl]benzenesulfamides, 2-aryl-5-R-, 2-aryl-5-R, 5-R1-5,6-dihydro- and 2-aryl-6'H-spiro[(cycloalkyl-, heterocyclil-, hetaryl-)]-[1,2,4]triazolo[1,5-c]quinazolines, 2-aryl-4a-R-5,6-dihydropirrolo-[1,2-a][1,2,4]triazolo[1,5-c]quinazoline-7(4aH)-ones, (2-R-7-oxo-4a,5,6,7-tetrahydropirrolo[1,2-a][1,2,4]triazolo[1,5-c]quinazoline-4a-yl)carboxylic acids and their esters. The dynamic equilibrium among tautomers was substantiated using quantumchemical calculations (ΔG values for conformers, comparison of calculated andexperimental UV-spectra for tautomeric forms) and spectral (UV-spectra, X-ray structural study) methods. The obtained data allowed to predict the regioselectivity of [5+1]-cyclo-condensation processes with different electrophiles. The strategy of purposeful search of hypoglycemic agents among products of 2-(3-aryl-1H-1,2,4-triazole-5-yl)phenyl]amines modification was elaborated. This strategy is based on combination of different hypoglycemic pharmacophores and was realized via synthesis of N-phenyl-N'-[2-(3-phenyl-1H-1,2,4-triazole-5-yl)phenyl]ureas and N-[2-(3-phenyl-1H-1,2,4-triazole-5-yl)phenyl]benzsulfamides. The series of novel 2-aryl-5-R- and 2-aryl-5-R1-5-R2-5,6-dihydro[1,2,4]triazolo-[1,5-c]quinazolines via [5+1]-cyclocondensation of [2-(3-aryl-1H-1,2,4-triazole-5-yl)-phenyl]amines with chloralhydrate, aldehydes and ketones (aliphatic and aromatic). It was established, that corresponding 5-monosubstituted 5,6-dihydro[1,2,4]triazolo[1,5-c]quinazolines undergoes spontaneous oxidation yielding available 5-(alkyl-,cycloalkyl-, aryl-)-[1,2,4]triazolo[1,5-c]quinazolines. It was found, that interaction of 2-phenyl-5-trichloromethyl-5,6-dihydro-[1,2,4]- triazolo[1,5-с]quinazoline with weak nucleophiles progresses under Е1СВ-mechanism yielding 5-dichloromethyl-2-phenyl-[1,2,4]triazolo[1,5-c]quinazoline. In the same time, interaction of 2-phenyl-5-trichloromethyl-5,6-dihydro-[1,2,4]triazolo[1,5-с]quinazoline with strong N-, O-nucleophiles led to the degradation of pyrimidine ring and formation of [2-(3-phenyl-1,2,4-triazol-5-yl)phenyl]amines. Novel 2-aryl-6'H-spiro[(cycloalkyl-, heterocyclil-, hetaryl-1(3,4),5]-[1,2,4]-triazolo[1,5-c]quinazolines were synthesizedvia [5+1]condensation of [2-(3-aryl-1H25 1,2,4-triazol)phenyl]amines with cyclic ketones, N-R-piperidin-3(4)-ones, dihydrothiophen-3(2H)-one, dihydro-2H-pyran-4(3H)-one, dihydro-2H-thiopyran-3(4H)-ones, isatineand in its derivatives. It was established, that interaction of 2-(3-aryl-1H-1,2,4-triazol-5-y)phenyl]amine with oxocarboxylic and dioxocarboxylic acids and their esters depending on a position of electrophilic centers led to the formation of 5-methyl-2-aryl-5,6-dihydro[1,2,4]- triazolo[1,5-c]quinazolin-5-carboxylic acids and their esters, ethyl 2-(2-aryl-5-methyl- 5,6-dihydro-[1,2,4]triazolo[1,5-c]quinazolin-5-yl)acetatesand 2-aryl-4a-R-5,6-dihydropyrrolo[1,2-a][1,2,4]triazolo[1,5-c]quinazoline-7(4aH)-ones. In the performance of this work, 138 compounds (126 for the first time) were synthesized. The compounds with antibacterial, fungicidal, antitumor, hypoglycemic, anticonvulsive activity and low toxicity were found among obtained substances. It was shown that, [2-(3-aryl-1,2,4-triazole-5-yl)phenyl]amines, their functional and annelated derivatives revealed antibacterial and antifungal activity. It was detected, that [2-(3-aryl-1,2,4-triazole-5-yl)phenyl]amines have MIC value in the range of 3,1-12,5 μg/ml against St. aureus and MFC value in the range of 12,5-50,0 μg/ml against C. albicans exceeding the activity of reference drugs Nitrofural and Ketokonazole. Conducted SAR-analysis for [2-(3-aryl-1H-1,2,4-triazole-5-yl)phenyl]amines showed, that antimicrobial activity was conditioned, as by heterocyclic fragment, sobyposition of substituent in phenyl moiety. Conducted study allowed to detect the agents with high hypoglycemic activity among series of [2-(3-aryl-1H-1,2,4-тtriazole-5-yl)phenyl]amines and their N-arylcarbamates and N-arylsulfamides. This part of the work may be considered as novel approach for purposeful synthesis of bioactive compounds among discussed heterocyclic system where in antidiabetic pharmacophores joined by «linker» phenyl fragments. SAR-analysis allowed to define the directions to the further modification of molecules aimed to the creation of novel hypoglycemic drugs. High anticonvulsant and neuroprotective activities of previously unknown 2-aryl-5-R,5-R1-5,6-dihydro- and 2-aryl-6'H-spiro[(cycloalkyl-, heterocyclil-, hetaryl-)]-[1,2,4]triazolo[1,5-c]quinazolines were established. It was found, that anticonvulsant activity of 5-R-2'-aryl-6'H-spiro[(indole-3,5-[1,2,4]triazolo[1,5-c]quinazoline]-2(1H)-ones on corazole-induced kindling model exceeded or was comparable with activity of the most widely used drugs (carbamazepine, lamotrigine) that is a weighty argument for study of novel spiro[1,2,4]triazolo[2,3-c]quinazolines as prospective antiepileptic agents.
[(3-Аryl-1H-1,2,4-triazol)phenyl]amines: synthesis, chemical modification, physico-chemical and biological properties of the synthesized compounds
Keywords: синтез; [2-(3-арил-[1,2,4]триазол-5-ил)феніл]аміни; таутомерія; 5-R(R1)-2-арил-5,6-дигідро-[1,2,4]триазоло[1,5-с]хіназоліни; спектральні характеристики; фармакологічний скринінг; synthesis; [2-(3-aryl-[1,2,4]triazole-5-yl)phenyl]amines; tautomerism; ureas; 5-R(R1)-2-aryl-5,6-dihydro-[1,2,4]triazolo[1,5-с]quinazolines; spectral characteristics; pharmacological screening